Tumescent technique as regional anesthesia - Stevkovska, Mare; Vasilevska Nikodinovska, Violeta (Scientific Foundation SPIROSKI, 2020)
Tumescent technique is a technique of infiltration a large volume of buffered low concentration of lidocaine and adrenaline in normosaline in the subcutaneous tissue. This solution that is easily and painlessly infiltrated, anesthetizes a large area of subcutaneous tissue in particular body areas like: abdomen, thigh or arms; it provides less bleeding during procedures performed on the skin and subcutaneous tissue. The tumescent local anesthesia (TLA) is a very simple and save procedure, widely used in many surgical branches. The aim of the paper was to assess the value of the tumescent local anesthesia during liposuction. Material and methods: Sixteen patients with a mean age of 32 years (24-46) underwent liposuction of one to three body areas, using tumescent technique, wide-awake. Тotal of 27 procedures were performed, with infiltration of solution of 0.075% lidocaine with 1:1,000,000 adrenaline and 25 ml of 8.4% sodium bicarbonate in 1000 ml normosaline, mean infiltrated solution of 2506 ml (1600-5000), mean dosage of lidocaine 25.9 mg/kg (18.88-50.6 mg/kg), total amount of lidocaine 2010 mg (1360-4000 mg). Results: TLA was successfully realized; 68.8% (11) of patients were happy and satisfied, 12.5% (2) of patients had headache and dizziness, in 12.5% (2) of patients the procedure was stopped because of a severe pain, one in the first region and one in the second region, and in 6.3% (1) of patients mild signs of lidocaine toxicity were observed. There were no complications that needed treatment or hospitalization; also, there were no lethal cases. Conclusion: Sole tumescent local anesthesia at a dosage 18-50 mg/kg lidocaine in prudent chosen patients seems to be safe regional anesthesia technique for the procedure of subcutaneous fat tissue.
TУМЕСЦЕНТНАТА ТЕХНИКА КАКО РЕГИОНАЛНА АНЕСТЕЗИЈА
Keywords: tumescent; lidocaine; anesthesia